The Contradictory Nature of the Ghost in Hamlet - Salami, Ismail (Richtmann Publishing, 2011)
The present study shows how Shakespeare seeks to manipulate the reader's response in Hamlet by using contradictions andambiguities and how the reader eventually reconstructs a palpable world in the impalpable world of the text. These contradictions compelthe reader to participate in the composition of the text and make him keep changing his own approach to the work with the result that themore he reads the play, the deeper he finds himself entrenched in contradictions. As he fails to grasp the logic of events, the reader relateshis own world to the text instead of relating the events to his world and recreates his own world. Therefore, he can easily detach himselffrom the text and let his imagination run loose as the play proves too vague for him to comprehend. Eventually, the reality achieved by thereader in the course of reading the play is only the reality, which dwells in the innermost recesses of his mind.